Data from: Multispecies genetic structure and hybridization in the Betula genus across Eurasia - Tsuda, Yoshiaki; Semerikov, Vladimir; Sebastiani, Federico; Vendramin, Giovanni Giuseppe; Lascoux, Martin (Dryad, 2016)
Boreal and cool temperate forests are the major land cover of northern Eurasia, and information about continental-scale genetic structure and past demographic history of forest species is important from an evolutionary perspective and has conservation implications. However, although many population genetic studies of forest tree species have been conducted in Europe or Eastern Asia, continental-scale genetic structure and past demographic history remain poorly known. Here, we focus on the birch genus Betula, which is commonly distributed in boreal and cool temperate forests, and examine 129 populations of two tetraploid and four diploid species collected from Iceland to Japan. All individuals were genotyped at seven to 18 nuclear simple sequence repeats (nSSRs). Pairwise math formula among the six species ranged from 0.285 to 0.903, and genetic differentiation among them was clear. structure analysis suggested that Betula pubescens is an allotetraploid and one of the parental species was Betula pendula. In both species pairs of B. pendula and B. plathyphylla, and B. pubescens and B. ermanii, genetic diversity was highest in central Siberia. A hybrid zone was detected around Lake Baikal for eastern and western species pairs regardless of ploidy level. Approximate Bayesian computation suggested that the divergence of B. pendula and B. platyphylla occurred around the beginning of the last ice age (36 300 years BP, 95% CI: 15 330–92 700) and hybridization between them was inferred to have occurred after the last glacial maximum (1614 years BP, 95% CI: 561–4710), with B. pendula providing a higher contribution to hybrids. The genotype files of multiple birch species in EurasiaTsuda_Betula_sampleInfo: This file includes a list of population code, name, country, longitude (E) and latitude (N) which are corresponding to "Tsuda_Betula1594_7loc_STRUCTURE.txt". Tsuda_Betula_TetDip_FSTAT: The genotype data for software FSTAT. To analyze diploid-tetraploid combined data keeping allele frequencies, tetraploid genotypes were ...